Analysis of selected policies towards universal health coverage in Uganda: the policy implementation barometer protocol - Ssengooba, Freddie; Hongoro, Charles; Rutebemberwa, Elizeus; Twalo, Thembinkosi; Mwendera, Chikondi; Douglas, Mbuyiselo; Mukuru, Moses; Kasasa, Simon (Archives of Public Health, 2018)
Policy implementation remains an under researched area in most low and middle income countries and it is not surprising that several policies are implemented without a systematic follow up of why and how they are working or failing. This study is part of a larger project called Supporting Policy Engagement for Evidence-based Decisions (SPEED) for Universal Health Coverage in Uganda. It seeks to support policymakers monitor the implementation of vital programmes for the realisation of policy goals for Universal Health Coverage. A Policy Implementation Barometer (PIB) is proposed as a mechanism to provide feedback to the decision makers about the implementation of a selected set of policy programmes at various implementation levels (macro, meso and micro level). The main objective is to establish the extent of implementation of malaria, family planning and emergency obstetric care policies in Uganda and use these results to support stakeholder engagements for corrective action. This is the first PIB survey of the three planned surveys and its specific objectives include: assessment of the perceived appropriateness of implementation programmes to the identified policy problems; determination of enablers and constraints to implementation of the policies; comparison of on-line and face-to-face administration of the PIB questionnaire among target respondents; and documentation of stakeholder responses to PIB findings with regard to corrective actions for implementation. Methods/Design: The PIB will be a descriptive and analytical study employing mixed methods in which both quantitative and qualitative data will be systematically collected and analysed. The first wave will focus on 10 districts and primary data will be collected through interviews. The study seeks to interview 570 respondents of which 120 will be selected at national level with 40 based on each of the three policy domains, 200 from 10 randomly selected districts, and 250 from 50 facilities. Half of the respondents at each level will be randomly assigned to either face-toface or on-line interviews. An integrated questionnaire for these interviews will collect both quantitative data through Likert scale-type questions, and qualitative data through open-ended questions. And finally focused dialogues will be conducted with selected stakeholders for feedback on the PIB findings. Secondary data will be collected using data extraction tools for performance statistics.
Keywords: Policy implementation barometer; Balanced score card; Uganda